Academic advisory system (ACADS) - Abdul Kadir, Amalina (2007)
Academic Advisory System (ACADS) is a web-based information system. It Academic Advisory is a system that provides assistance and guidance to the students in the aspects of education, teaching, learning and assessment to ensure academic excellence. Several steps involved in producing Academic Advisory System. The steps include registration, determining students’ progress coursework, examination, and reporting. The main user of this system is academic advisor. The methodology used is System Analysis and Design (SADM). For the initial finding, this project cover As-Is business process and data model, To-Be business process and data model, user requirements, database design, system architecture, and user interface design. From the problem analysis of current business process, there are weaknesses and constraints in the implementation of academic advisory system. Consequently, this system requires long time and lots of efforts because several support functions for ACADS has to develop first. Hopefully, the implementation of ACADS can help organizations in organizing and maintaining students’ performance.